Optimized Electrode Placements for Non-invasive Electrical Stimulation of the Olfactory Bulb and Olfactory Mucosa - Cakmak, Yusuf Ozgur; Nazim, Kamran; Thomas, Chris; Datta, Abhishek (Frontiers in Neuroscience, 2020)
The olfactory system is known to be dysfunctional in the early stages of Parkinson’s Disease (PD) and Alzheimer’s disease (AD). It is also shown that intact olfactory function can be a key role player for regaining consciousness after brain injuries. Modulation of the olfactory regions have been attempted successfully with electrical stimulation over the years, either directly (transethmoidally, intraoperatively, intranasally, etc.) or indirectly through the vagus nerve. We sought to develop a means of delivering optimized direct electrical stimulation to the olfactory region in a non-invasive fashion and in a way that is simpler, easier, and less cumbersome. The ultimate goal was to develop a system that would allow easier testing in future clinical trials presenting an opportunity to fully develop this potential treatment option. We devised six potential electrode placements leveraging commonly accepted facts of electrical stimulation, easier access through relatively higher conductive pathways into the brain, and practicality. Using an ultra-high resolution finite element model, we screened each one of these montages for their ability to target the olfactory regions primarily and thereafter for some subcortical regions implicated in the pathogenesis of PD and AD. Modelling results indicate that some placements do result in inducing meaningful electric field magnitudes in the regions of interest. A practical headgear concept is proposed to realize the most ideal configuration. Our results pave the way for developing the first non-invasive electrical stimulation wearable system for targeting the olfactory regions which can help to alleviate the symptoms or suppress the progression of these neurological disorders.